Going Global: A Glimpse into the Language Identity and Experiences of Filipino English Teachers Abroad - Flores, Kathleen B. (8ISC Proceedings: Arts and Education, 2022)
The past two decades brought increased interest in the study of identity in the field of language education. Numerous studies on language teacher identity mostly center on professional identity and are concentrated on participants from the expanding circle. Studies on English teachers’ language identity from the outer circle like the Philippines are scarce, even more so among those residing and teaching abroad. Drawing on the relatively new theoretical frameworks of Norton (Peirce, 1995) and Bucholtz and Hall (2005) on identity, investment, and interaction, this study investigated the language identity and experiences of Filipino English teachers working abroad. Eight English teachers living and working abroad were purposively selected to take part in the study. Five English teachers met the selection criteria. Narrative inquiry through interviews and stories is utilized to gather data, and thematic analysis based on Braun and Clarke’s (2006) six-phase framework is employed to analyze the data collected. The results revealed participants’ perceptions of English and nativeness, their language identity, and language experiences that include opportunities, challenges, and coping strategies. Moreover, participants’ exposure to and interaction with other English speakers influence how they view themselves as language speakers, and their language-related experiences continue to [re]shape their language identities. It is therefore recommended that English education majors are provided with opportunities to [re]construct and analyze their language identities while still in school. Keywords : teaching English, nativeness, English ownership, language education, internationalization